Factors Affecting Job Satisfaction Among Community-Pharmacists with VIJS Instrument in South Sulawesi - Pawallangi, Andi Nur'ainun Reskia; Prabandari, Yayi Suryo; Trung, Vo Quang; Kristina, Susi Ari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: Pharmacists' responsibilities have shifted over time. Pharmacists have grown increasingly clinically involved in patient care from delivering pharmaceuticals throughout the healthcare system. These developments may have influenced pharmacists' job satisfaction. This is significant since performance, motivation, and productivity are positively associated with job happiness, whereas a lack of job satisfaction may hurt patient care and safety and increase job turnover.Objectives: To analyze the factors affecting job satisfaction among community pharmacists in South Sulawesi.Methods: This research uses quantitative and analytical observational research with a cross-sectional study design. This research was conducted from mid-January to mid-March of 2024, with the research subject being community pharmacists who worked at pharmacies, primary healthcare, and clinics in the South Sulawesi region. Research instruments are distributed to each IAI branch management in South Sulawesi via Google Forms. The instruments used in this research were sociodemography, pharmacist service characteristics, and the job satisfaction questionnaire (VIJS Instrument). The analysis used is univariate analysis (descriptive), bivariate analysis (independent T-test), and multivariate analysis (multiple regression linear analysis).Results: The general result of this research is satisfied based on the mean score (3.8±0.8). The lowest mean score from both factors is monthly income (3.1±1.1) and learning and advancement opportunity (3.3±1.1). The regression analysis indicated that factors affecting job satisfaction among community pharmacists in South Sulawesi are monthly income (p=0.025), working period (p=0.019), number of patients per day (p=0.008), and number of prescriptions per day (p=0.005).Conclusion: Community pharmacists in South Sulawesi are satisfied with their work, and their satisfaction level is affected by monthly income, working period, the number of patients per day, and the number of prescriptions per day.